Pengembangan Kualitas Sumber Daya Guru dan Karyawan Melalui Penerapan Manajemen Peningkatan Mutu Berbasis Revitalisasi Profil Pelajar Pancasila - Suryati Suryati (Departement of Mathematics Education, 2021)
The main purpose of this action research is to find out the development of the quality of human resources for teachers and employees through the implementation of quality improvement management based on Pancasila Student Profile Revitalization at SD Negeri Kedurus I Surabaya. Responding to the current Covid-19 pandemic conditions, learning in the new academic year 2021/2022 is dynamic in nature referring to the policy on the Implementation of Community Activity Restrictions (PPKM) in each region, and the Joint Decree (SKB) of 4 Ministers on Guidelines for Implementation of Learning in a Pandemic Period. Covid-19. In the midst of these circumstances, schools are required to play a driving role or locomotor in the process of forming the Pancasila Student Profile which is a manifestation of the idealism of a series of characteristics inherent in students as a result of effective educational and learning interventions. Indeed, education plays a very important role in the process of improving the quality of human resources. Improving the quality of education is a process that is integrated with the process of improving the quality of human resources itself. The implementation of the quality improvement management is through the mechanism of 4 (four) cycles of action carried out on 30 teachers and employees at SD Negeri Kedurus I Surabaya. Based on the explanation of the research data above, it can be concluded that the implementation of quality improvement management based on the Pancasila Student Profile Revitalization has proven to be effective in improving the quality of human resources for teachers and employees at SD Negeri Kedurus I Surabaya. This is indicated by the high achievement of the indicators for implementing MPM and improving the quality of human resources for teachers and employees and moving progressively from a score of 2.5 or 63% with 38% completeness at the beginning of the cycle to 3.2 or 81% with 100% completeness at the end of the cycle.